Export Destination, Product Quality and Wages in a Middle‐Income Country. The Case of South Africa. Issue 1 (22nd January 2013) - Rankin, Neil; Schöer, Volker
Abstract A robust finding in the firm‐level literature is that exporting firms pay higher wages. Using South African data this paper investigates the relationship between export destination and wages at a worker level. South Africa, a middle‐income country, has two distinct main export markets—a regional market where per capita incomes are lower than at home, and an international market with higher per capita incomes. Our estimates show that workers in firms that export to the region earn less than those that produce for the domestic market. Those in firms that export outside the region earn more than either domestic producers or region‐only exporters. Much of this difference in wages can be explained by the premium the different types of exporters pay for skills. These results support previous studies which suggest that export destination is related to product quality which in turn is related to worker quality and therefore wages.